The Transformation of Judicial Supervision: Tracing the Legacy of Qadhi al-Qudhah in Shaping Indonesia’s Modern Judicial Commission - Diah Kusuma; Irwantoni Irwantoni; Eti Karini (CV. Dyoqu Publishing and Management, 2025)
Background: The practice of judicial oversight plays a central role in maintaining the credibility of a legal system. In Indonesia, this function has evolved through institutional reforms and bears conceptual resemblance to historical Islamic governance, particularly the role of Qadhi al-Qudhah. Aims: This study explores how Indonesia’s Judicial Commission functions in overseeing judges, and examines to what extent its authority aligns with or departs from the supervisory principles embedded in Fiqh Siyasah. The comparison aims to deepen understanding of ethical control in both classical and contemporary contexts. Method: The research applies a doctrinal legal method grounded in literature review. Primary sources include Indonesian statutory laws and Islamic jurisprudential texts, analyzed through comparative interpretation to reveal thematic convergence and divergence between the two systems. Result: The study finds that while both the Judicial Commission and Qadhi al-Qudhah serve to uphold ethical standards among judges, their scope of action differs markedly. The Commission’s external nature and advisory status limit its effectiveness compared to the integrated and authoritative position held by Qadhi al-Qudhah within Islamic governance. Conclusion: Despite structural differences, the core mission of ensuring justice and judicial integrity unites both models. Adopting foundational values from Islamic political jurisprudence may enrich Indonesia’s current oversight system, reinforcing its legitimacy and moral grounding.